Perceptions and observations of shared decision making during pediatric otolaryngology surgical consultations - Yolanda Evong; Jill Chorney; Gilanders Ungar; Paul Hong (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective Increased parental involvement in the decision-making process when considering elective surgeries for their children, termed shared decision-making (SDM), may lead to positive outcomes. The objective of this study was to describe perceived and observed levels of SDM during pediatric otolaryngology consultations. Methods One hundred and seventeen parents and their children undergoing elective surgical consultations were prospectively enrolled. The visits were videotaped and coded using the Observing Patient Involvement (OPTION) scale. Following the encounter, all participants completed a questionnaire that measured perceived levels of SDM (SDM-Q-9). Surgeons also completed a similar questionnaire (SDM-Q-Doc). Spearman’s correlation coefficient was determined to measure the associations between observed and perceived levels of SDM. Results The overall OPTION scores were low (median score of 14 out of 48) and not significantly correlated with perceived levels of SDM (SDM-Q-9, p = 0.415; SDM-Q-Doc, p = 0.236), surgery type (p = 0.197), or patient demographic factors. The OPTION scores were positively correlated with consultation length (p < 0.001). There was great variability in the level to which each OPTION items were observed during the consultation (not present in any visits to present in 96.6% of the visits). Conclusions Observed levels of SDM were consistently low, but higher levels were observed when the surgeon spent more time during the consultation. Observed levels of SDM did not match perceived levels of SDM, which were consistently rated higher by both caregivers and surgeons.